Stage IV Small Lymphocytic Lymphoma Presenting with Unilateral Vision Loss - Christopher Le; Adam Jacob; Devarajan Iyengar; John Dedousis; Antonios Tsompanidis (Case Reports in Oncological Medicine)
Small lymphocytic lymphoma (SLL) is a manifestation of chronic lymphocytic leukemia (CLL) in which malignant B-cell lymphocytes accumulate in the lymph nodes or bone marrow. In this report, we describe the medical course of a patient diagnosed with stage IV small cell lymphocytic lymphoma, who presented to the emergency room with acute neurologic manifestations of SLL.